Toxicidade de compostos químicos derivados de fenol natural em bioensaios vegetais - Costa, Thaís Lazarino Maciel da (2023)
Excessive use of herbicides causes problems such as impacts on human health, environmental pollution and plant resistance to conventional herbicides. Research is seeking safer and more effective alternatives, such as natural compounds, semi-synthetic derivatives and essential oils. This study focused on the evaluation of the toxicity and genotoxicity of synthetic molecules derived from thymol and rosemary essential oil, both rich in thymol. All compounds were subjected to phytotoxic and cytotoxic activity tests using Lactuca sativa and Sorghum bicolor as model plants. In addition, the genotoxicity of rosemary oil was evaluated through molecular analyses with ISSR markers. The germination percentage, germination speed index, aerial and root length of seeds and seedlings subjected to treatments were evaluated. Molecules containing chlorine in the para position of the thymoxy group exhibited phytotoxic and cytogenotoxic effects superior to those of the commercial herbicides 2,4-D and glyphosate. Concentrations of 0.01 and 0.0050 mmol. L-1 of rosemary essential oil promoted greater toxicity responses for both lettuce and sorghum, presenting a clastogenic and aneugenic mechanism of action. Molecular analyses demonstrated equality between the genomic stability of plants treated with the tested positive controls and the different concentrations of the oil. The results demonstrate the phytotoxic, cytotoxic and genotoxic effects of the synthetic molecules and the rosemary essential oil.